2017
DOI: 10.1002/cmdc.201700349
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research Advances in Selective Matrix Metalloproteinase‐13 Inhibitors as Anti‐Osteoarthritis Agents

Abstract: Matrix metalloproteinase-13 (MMP-13) plays a key role in the degradation of type II collagen in cartilage and bone in osteoarthritis (OA). The subtle differences between the S1' loop of MMP-13 and that of other MMPs offer a structural base for the design of selective MMP-13 inhibitors to mitigate the unperceived risk associated with inhibiting other MMP isoforms. In this review, we summarize zinc-binding and non-zinc-binding selective MMP-13 inhibitors. The zinc-binding MMP-13 inhibitors contain a small set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 73 publications
1
48
0
Order By: Relevance
“…Since their discovery, MMPs have emerged as an intriguing target in pharmaceutical research . Due to the involvement of members of the MMP family in a multitude of severe diseases, such as cancer, arthritis, chronic obstructive pulmonary disease (COPD), or sepsis, great efforts were taken to modulate MMP activity to possibly treat diseases in which MMP activity is out of balance . Due to side effects evolving from a lack of selectivity and insufficient knowledge about the relevance of the target family in pathological processes, no compound designed as an MMP inhibitor has reached the market so far, and clinical trials have failed .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their discovery, MMPs have emerged as an intriguing target in pharmaceutical research . Due to the involvement of members of the MMP family in a multitude of severe diseases, such as cancer, arthritis, chronic obstructive pulmonary disease (COPD), or sepsis, great efforts were taken to modulate MMP activity to possibly treat diseases in which MMP activity is out of balance . Due to side effects evolving from a lack of selectivity and insufficient knowledge about the relevance of the target family in pathological processes, no compound designed as an MMP inhibitor has reached the market so far, and clinical trials have failed .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Due to the involvement of members of the MMP family in am ultitude of severe diseases, such as cancer, [10][11][12][13][14][15][16] arthritis, [17,18] chronic obstructive pulmonary disease (COPD), [19][20][21] or sepsis, [22][23][24][25] great efforts weret aken to modulate MMP activity to possibly treat diseases in which MMP activity is out of balance. [26,27] Due to side effects evolving from al ack of selectivity and insufficient knowledge aboutt he relevance of the target family in pathological processes, no compound designed as an MMP inhibitor has reached the market so far,a nd clinicalt rials have failed. [28] Doxycycline, an antibiotic tetracycline that exhibitso ff-target inhibition of MMP-7a nd MMP-8, is the only compound approved as aM MP inhibitor for the treatment of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…32) Administration of specific MMP-13 inhibitors significantly reduced the severity of the pathology in both human and animal models of OA. 33,34) Resveratrol, a natural antioxidant, reduced MIA-induced pain by inhibiting MMP-13 mRNA expression and inflammatory cytokines in rats. 35) Our previous study showed that GCSB-5, a herbal formulation, protected against articular cartilage destruction by suppressing MMP-2 activity and cyclooxygenase-2 expression in a MIA-induced OA rat model.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of MMP activity in cartilage tissues is caused an imbalance between the catabolism and the anabolism of chondrocytes, which leads to the irreversible degradation of COL2A1 and proteoglycans, essential constituents of the ECM responsible for the protection of articular cartilage and chondrocytes [Goldring et al, 2011;Heinegard and Saxne, 2011]. MMP-3 and MMP-13, in particular, are key players in the catabolic processes of OA, and they decompose aggrecan and COL2A1 which provide elasticity to the cartilage and aid shock relaxation [Wang et al, 2013;Xie et al, 2017]. Many researchers have reported the inhibition or delay of the effects of degenerative arthritis by inhibiting MMP-13 expression and suggest that the suppression of MMP-13 is very important for the mitigation of OA [Kim et al, 2011;Wang et al, 2013;Xie et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…MMP-3 and MMP-13, in particular, are key players in the catabolic processes of OA, and they decompose aggrecan and COL2A1 which provide elasticity to the cartilage and aid shock relaxation [Wang et al, 2013;Xie et al, 2017]. Many researchers have reported the inhibition or delay of the effects of degenerative arthritis by inhibiting MMP-13 expression and suggest that the suppression of MMP-13 is very important for the mitigation of OA [Kim et al, 2011;Wang et al, 2013;Xie et al, 2017]. ADAMTS-4 is considered the primary enzyme responsible for the degradation of aggrecan during the pathogenesis of OA [Majumdar et al, 2007].…”
Section: Discussionmentioning
confidence: 99%